KONSEP KEBAHAGIAAN DALAM PERSPEKTIF AL-FARABI - Endrika Widdia Putri (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2018)
The concept of happiness is the eternal concept that always be contemporer thing, it means that the concept of happiness will never run out of the discussion and will always be the contemporary issues. People in the past, today, and in the future they will have the same orientation about the happiness. The concept of happiness is indeed not new in the world of philosophy and sufism, so it has several experiences in the dynamics of the development.  Al-Farabi was a Muslim and philosopher who discussed the concept of happiness. Although, al-Farabi was not the first person who discussed this concept, al-Farabi had his own concept in explaining happiness and had different with the previous philosophers. Happiness according to al-Farabi is the kindness who desired for good itself. Second, there are four ways to obtain happiness according to al-Farabi, namely intention and will, understanding of good deeds, having four virtues, and having a central virtue (moderate). Third, the moral and happiness relationship according to al-Farabi has  good character is a sign that person’s soul is healthy, if a person’s soul is healthy it means that he/she can enjoy various kinds of spritual happiness.